Transdermal oestradiol for androgen suppression in prostate cancer: long-term cardiovascular outcomes from the randomised Prostate Adenocarcinoma Transcutaneous Hormone (PATCH) trial programme. Issue 10274 (13th February 2021) - Langley, Ruth E; Gilbert, Duncan C; Duong, Trinh; Clarke, Noel W; Nankivell, Matthew; Rosen, Stuart D; Mangar, Stephen; Macnair, Archie; Sundaram, Subramanian Kanaga; Laniado, Marc E; Dixit, Sanjay; Madaan, Sanjeev; et al.
Summary: Background: Androgen suppression is a central component of prostate cancer management but causes substantial long-term toxicity. Transdermal administration of oestradiol (tE2) circumvents first-pass hepatic metabolism and, therefore, should avoid the cardiovascular toxicity seen with oral oestrogen and the oestrogen-depletion effects seen with luteinising hormone releasing hormone agonists (LHRHa). We present long-term cardiovascular follow-up data from the Prostate Adenocarcinoma Transcutaneous Hormone (PATCH) trial programme. Methods: PATCH is a seamless phase 2/3, randomised, multicentre trial programme at 52 study sites in the UK. Men with locally advanced or metastatic prostate cancer were randomly allocated (1:2 from August, 2007 then 1:1 from February, 2011) to either LHRHa according to local practice or tE2 patches (four 100 μg patches per 24 h, changed twice weekly, reducing to three patches twice weekly if castrate at 4 weeks [defined as testosterone ≤1·7 nmol/L]). Randomisation was done using a computer-based minimisation algorithm and was stratified by several factors, including disease stage, age, smoking status, and family history of cardiac disease. The primary outcome of this analysis was cardiovascular morbidity and mortality. Cardiovascular events, including heart failure, acute coronary syndrome, thromboembolic stroke, and other thromboembolic events, were confirmed using predefined criteria and source data. Sudden or unexpected deaths were attributed to a cardiovascular category if a confirmatory post-mortem report was available and as other relevant events if no post-mortem report was available. PATCH is registered with the ISRCTN registry, ISRCTN70406718; the study is ongoing and adaptive. Findings: Between Aug 14, 2007, and July 30, 2019, 1694 men were randomly allocated either LHRHa (n=790) or tE2 patches (n=904). Overall, median follow-up was 3·9 (IQR 2·4–7·0) years. Respective castration rates at 1 month and 3 months were 65% and 93% among patients assigned LHRHa and 83% and 93% among those allocated tE2. 157 events from 145 men met predefined cardiovascular criteria, with a further ten sudden deaths with no post-mortem report (total 167 events in 153 men). 26 (2%) of 1694 patients had fatal cardiovascular events, 15 (2%) of 790 assigned LHRHa and 11 (1%) of 904 allocated tE2. The time to first cardiovascular event did not differ between treatments (hazard ratio 1·11, 95% CI 0·80–1·53; p=0·54 [including sudden deaths without post-mortem report]; 1·20, 0·86–1·68; p=0·29 [confirmed group only]). 30 (34%) of 89 cardiovascular events in patients assigned tE2 occurred more than 3 months after tE2 was stopped or changed to LHRHa. The most frequent adverse events were gynaecomastia (all grades), with 279 (38%) events in 730 patients who received LHRHa versus 690 (86%) in 807 patients who received tE2 (p<0·0001) and hot flushes (all grades) in 628 (86%) of those who received LHRHa versus 280 (35%) who received tE2 (p<0·0001). Interpretation: Long-term data comparing tE2 patches with LHRHa show no evidence of a difference between treatments in cardiovascular mortality or morbidity. Oestrogens administered transdermally should be reconsidered for androgen suppression in the management of prostate cancer. Funding: Cancer Research UK, and Medical Research Council Clinical Trials Unit at University College London.